Β-Lactam resistance among Haemophilus influenzae isolates in Poland. (December 2017) - Kiedrowska, Marlena; Kuch, Alicja; Żabicka, Dorota; Waśko, Izabela; Ronkiewicz, Patrycja; Wasiak, Katarzyna; Bojarska, Katarzyna; Hryniewicz, Waleria; Skoczyńska, Anna
Highlights: Haemophilus influenzae resistance to β-lactam antibiotics requires continuous attention. The algorithm proposed by NordicAST can be applied in routine laboratory work. Sequencing of the ftsI gene is useful in molecular epidemiology studies. Abstract: Objectives: Haemophilus influenzae is a human-specific Gram-negative coccobacillus responsible for a significant number of respiratory tract infections and severe invasive infections such as meningitis and sepsis. The purpose of this study was to characterise the mechanisms of β-lactam resistance among Polish H. influenzae isolates and to evaluate the resistance detection methods applied. Methods: This study was conducted on 117 Polish H. influenzae isolates collected in 2012. Minimum inhibitory concentrations were assessed by broth microdilution. All strains were evaluated using the disk diffusion method and the algorithm proposed by the Nordic Committee on Antimicrobial Susceptibility Testing (NordicAST). To detect changes in penicillin-binding protein 3 (PBP3), PCR screening was performed, followed by ftsI gene sequencing. Results: Neither β-lactamase production nor PBP3 alterations were demonstrated in 76 isolates (65.0%). Susceptibility to ampicillin, amoxicillin, amoxicillin/clavulanic acid, cefuroxime (intravenous) and ceftriaxone was observed in 70.9%, 78.6%, 98.3%, 82.9% and 100% of the isolates, respectively. β-Lactamase production characterised 21 isolates (17.9%). Screening PCR identified 20 isolates (17.1%) with PBP3 alterations, and according to subsequent ftsI sequencing all these strains were finally recognised as gBLNAR (genetically β-lactamase-negative, ampicillin-resistant), among which 65.0% were ampicillin-resistant. According to molecular classification of PBP3 alterations, 95.0% of gBLNAR belonged to group II, representing four subgroups IIa–IId. Conclusions: Haemophilus influenzae resistance to antibiotics requires continuous attention, effective detection methods and a rational policy of antibiotic usage. The algorithm proposed by NordicAST can be applied in routine laboratory work, whereas sequencing of the ftsI gene may be useful in molecular epidemiology studies.